2020
DOI: 10.7759/cureus.11368
|View full text |Cite
|
Sign up to set email alerts
|

CALL Score and RAS Score as Predictive Models for Coronavirus Disease 2019

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a novel infectious disease of multi-system involvement with significant pulmonary manifestations. So far, many prognostic models have been introduced to guide treatment and resource management. However, data on the impact of measurable respiratory parameters associated with the disease are scarce. Objective: To demonstrate the role of Comorbidity-Age-Lymphocyte count-Lactate dehydrogenase (CALL) score and to introduce Respiratory Assessment Scoring (RAS) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 21 publications
2
27
1
1
Order By: Relevance
“…Similarly, when the model was evaluated in the Italian population, the CALL score’s predictive power as a predictor of hospital mortality was good (AUC 0.768, IC95%: 0.705 to 0.823), differing from our result[8]. And in another study conducted in Pakistan, the call score was strongly associated with progression and mortality in patients with COVID-19[9]. The results show the importance of evaluating the validity of the clinical prediction rules developed in other countries for use in our population.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, when the model was evaluated in the Italian population, the CALL score’s predictive power as a predictor of hospital mortality was good (AUC 0.768, IC95%: 0.705 to 0.823), differing from our result[8]. And in another study conducted in Pakistan, the call score was strongly associated with progression and mortality in patients with COVID-19[9]. The results show the importance of evaluating the validity of the clinical prediction rules developed in other countries for use in our population.…”
Section: Discussioncontrasting
confidence: 89%
“…In studies comparing scoring systems in COVID-19 patients, the effects of comorbidity and symptoms on mortality were also evaluated. Kamran et al suggested that comorbidity was not area under the curve: (p = 0.565) for mortality (7) while another study evaluating 52 intensive care patients with COVID-19 reported a relationship between advanced age and comorbidities and mortality (8). Zhang et al, examined 80 patients and found a significant relationship between cardiac diseases and hypertension and mortality (9) whereas Zhu et al retrospectively observed that among 181 patients with COVID-19, comorbidities were not predictive of mortality (10).…”
Section: Resultsmentioning
confidence: 99%
“…The CALL scoring system involves the evaluation of comorbidities, age, lymphocyte, and lactate dehydrogenase, which have been emphasized to play a role in COVID-19 since the emergence of the disease, and studies have been conducted to investigate the effect of these parameters on mortality. In a study examining 252 patients with COVID-19, it was shown that CALL was a reliable model for predicting mortality and determining the progression of the disease (7). In another study, Grifoni et al similarly determined that CALL was a reliable model for predicting mortality in patients with COVID-19 but noted that it did not show disease progression at a sufficient level (19).…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 20 It has been shown that the CALL score is an accurate and easy to use model for predicting the risk of progression in patients with COVID-19. 5 , 21 Therefore, we evaluated the effect preemptive hospitalization had on patient outcomes when stratifying patients by CALL score. In patients at a higher risk of disease progression (CALL score ⩾8), there were significantly fewer patients requiring HFNC (23.2% versus 44.2%), admission to the ICU (11.9% versus 23.9%) or IMV (11.9% versus 22.5%) when compared with patients who were not preemptively hospitalized.…”
Section: Discussionmentioning
confidence: 99%